Biomechanical comparison of tenodesis reconstruction for subtalar instability: a finite element analysis - Can, Xu (BMC Musculoskelet Disord, 2020)
BACKGROUND: There are several types of tenodesis reconstruction designed for subtalar instability. However, no comprehensive comparison has been conducted among these procedures in terms of their correcting power so far. The objective of this study is to evaluate the biomechanical behaviors of 5 representative procedures through finite element analysis. METHODS: Finite element models were established and validated based on one of our previous studies. The Pisani interosseous talocalcaneal ligament (ITCL) reconstruction, Schon cervical ligament (CL) reconstruction and Choisne calcaneofibular ligament (CFL) reconstruction were compared on the model with the CFL, ITCL and CL sectioned. The Schon triligamentous reconstruction and Mann triligamentous reconstruction were compared on the model with the CFL, ITCL and CL, as well as the ATFL sectioned. The inversion and external/internal rotation were quantified at different ankle positions based on the rotational moment. Then, the stress in ligaments and reconstructed grafts and the contact characteristics of the subtalar joint under inversional stress test were calculated and compared accordingly. RESULTS: For single ligament reconstruction, the Choisne CFL reconstruction provided the greatest degree of correction for subtalar instability, followed by the Schon CL reconstruction and then the Pisani ITCL reconstruction. For triligamentous reconstruction, the Mann procedure outperformed the Schon procedure in alleviating the subtalar instability. CONCLUSION: The finite element analysis showed that the Choisne CFL reconstruction and Mann triligamentous reconstruction provided the greatest degree of immediate postoperative subtalar stability. However, both procedures could not restore the biomechanical behaviors of the subtalar joint to normal. The long-term efficacy of these procedures warrants further investigation using a substantially larger sample of clinical cases.